Pirro Ligorio's worlds : antiquarianism, classical erudition and visual arts in the late Renaissance - Loffredo, Fernando; Loffredo, Fernando; Vagenheim, Ginette; Vagenheim, Ginette (Brill's studies in intellectual history, 2019)
Pirro Ligorio's antiquarian philology / Robert W. Gaston -- Looking for sirens : ancient sites in Naples according to Pirro Ligorio / Anna Schreurs -- Pirro Ligorio and sculpture, or, On the reproducibility of antiquity / Fernando Loffredo